Atopic Dermatitis, Sleep, and the COVID-19 Pandemic - Priscila Vernizi Roth; Renata Drizlionoks; Rafaela Cachiolo Antunes; Ana Chrystina Souza Crippa; Mariana Aparecida Pasa Morgan; Vânia Oliveira de Carvalho (Sleep Science)
Objective To investigate sleep disorders among children with atopic dermatitis (AD), before and during the coronavirus disease 2019 (COVID-19) pandemic.